2021
DOI: 10.2174/1386207323666200806164635
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Molecular Mechanism of Maxingyigan Decoction Against COVID-19: Network Pharmacology-based Strategy

Abstract: Aim and Objective: Maxingyigan (MXYG) decoction is a traditional Chinese medicine (TCM) prescription. However, how MXYG acts against coronavirus disease 2019 (COVID-19) is not known. We investigated the active ingredients and the therapeutic targets of MXYG decoction against COVID-19. Methods: A network pharmacology strategy involving drug-likeness evaluation, prediction of oral bioavailability, network analyses, and virtual molecular docking were used to predict the mechanism of action of MXYG against COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Three of the studies evaluated for data extraction (Glinsky [40], Ruan et al [41] Wang et al [42]) used some flavonoids to build molecular maps guided by genomic regulatory elements by analyzing gene silencing and overexpression experiments. Quercetin was a flavonoid identified as a supposed mitigation agent for COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies evaluated for data extraction (Glinsky [40], Ruan et al [41] Wang et al [42]) used some flavonoids to build molecular maps guided by genomic regulatory elements by analyzing gene silencing and overexpression experiments. Quercetin was a flavonoid identified as a supposed mitigation agent for COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“… Mechanisms: anti-inflammatory and immunity-based actions involving activation of T cells, lymphocytes, and leukocytes, as well as cytokine-cytokine-receptor interaction, and chemokine signaling pathways. [59] Cold-Damp Plague Formula TCMSP; TCMID; Swiss ADME; STITCH; GeneCards; STRING; Cytoscape; Key targets: IL6, TNF, IL10, MAPK8, MAPK3, CXCL8, CASP3, PTGS2, TP53, and MAPK1. KEGG signaling pathways: TNF signaling pathway, MAPK signaling pathway, Fc epsilon RI signaling pathway, toxoplasmosis, leishmaniasis, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Different from this, some scholars have found that Maxingyigan Decoction (MXYGD) for the treatment of COVID-19 contains three key components quercetin, luteolin, and formononetin, and also has three pivotal target genes, namely IL4, IL6, and CASP3, the results of molecular docking validation showed that the IL6 receptor and quercetin had the highest docking score, and the other three key components scored higher than Ribavirin. MXYGD plays an important role in the treatment and prevention of COVID-19 by activating leukocytes, T cells, lymphocytes, and other immune and anti-inflammatory effects ( Wang, et al, 2021b ). Today, Lianhua Qingwen Capsule has achieved good efficacy in the clinical treatment of COVID-19, which is also recognized by many scholars around the world ( Zheng, et al, 2020a ).…”
Section: The Application Of Network Pharmacology In the Study Of Tcm ...mentioning
confidence: 99%